2008 47th IEEE Conference on Decision and Control 2008
DOI: 10.1109/cdc.2008.4739424
|View full text |Cite
|
Sign up to set email alerts
|

On the state-space design of optimal controllers for distributed systems with finite communication speed

Abstract: We consider the problem of designing optimal distributed controllers whose impulse response has limited propagation speed. We introduce a state-space framework in which such controllers can be described. We show that the optimal control problem is not convex with respect to certain state-space design parameters, and demonstrate a reasonable relaxation that renders the problem convex. This relaxation is associated with an iterative numerical scheme known as the Steiglitz-McBride (SM) algorithm. We improve the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The synthesis of distributed controllers for interconnected systems has received considerable attention in recent years [1]- [12]. Particular motivation to search for 'localized' controllers comes from [1], where it was shown that optimal controllers for spatially-invariant systems, although centralized, have an inherent spatial-decay property.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of distributed controllers for interconnected systems has received considerable attention in recent years [1]- [12]. Particular motivation to search for 'localized' controllers comes from [1], where it was shown that optimal controllers for spatially-invariant systems, although centralized, have an inherent spatial-decay property.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years a body of literature has been developed that addresses the problem of distributed control of interconnected systems [1]- [13]. The present work is motivated by [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis problem of distributed control for interconnected systems has received considerable attention in recent years [1]- [14]. For linear spatially invariant plants, it was shown in [1] that optimal controllers are themselves spatially invariant.…”
mentioning
confidence: 99%